Formation during glycine-nitrate combustion and magnetic properties of YFe1–xNixO3 nanoparticles - Evgenia I. Lisunova; Nikolai S. Perov; Valentina O. Mittova; Boris V. Sladkopevtsev; Vuong Bui Xuan; Tien Nguyen Anh; Yulia A. Alekhina; Viktor F. Kostryukov; Irina Ya. Mittova (Конденсированные среды и межфазные границы, 2023)
The synthesis of FeO3 and YFe1–xNixO3 (x = 0.1; 0.15; 0.2; 0.3; 0.5) nanocrystals was performed under the conditions of a self-propagating wave of glycine-nitrate combustion and their characterization and determination of the effect of Ni2+ doping of yttrium ferrite on the magnetic properties of nanopowders. The technology for the synthesis of yttrium orthoferrite nanoparticles (with and without doping with Ni2+ ions) by the glycine-nitrate combustion method at a ratio of G/N = 1 and 1.5 without adding a gelling agent to the reaction mixture and using ethylene glycol/glycerol is described. For the characterization of nanopowders based on YFeO3, the following were determined: phase composition and crystal structure (X-ray diffraction (XRD) method); size and structure of nanocrystal particles (transmission electron microscopy (TEM)); elemental composition of the samples (local X-ray spectral microanalysis (LXSMA)); magnetic characteristics (field dependences of specific magnetization). Thermal annealing of the synthesized samples at 800°C for 60 min led to the formation of the о-YFeO3 main phase. Undoped samples of yttrium orthoferrite were characterized by a particle diameter in the range of 5-185 nm, depending on the gelling agent used. YFe1-xNixO3 particles had a predominantly round shape with a size of 24 to 31 nm; the non-monotonic dependence of the average particle diameter on the dopant content was revealed: as the amount of dopant added increased, the average crystallite size tended to decrease. Nanopowders of undoped yttrium orthoferrite exhibit antiferromagnetic behaviour of magnetic susceptibility with temperature. The change in the magnetic properties of the nickel-doped YFeO3 nanocrystalline powders was due to the incorporation of Ni2+ into the Fe3+position, which led to the formation of a material with more pronounced soft magnetic properties at a substitution degree of 0.1. Samples with high degrees of substitution (x = 0.15 and 0.3) were also characterized by paramagnetic behaviour at temperatures above 100 K.